MRI-Based Demonstration of the Normal Glymphatic System in a Human Population: A Systematic Review - Lee, Min Kyoung; Cho, Se Jin; Bae, Yun Jung; Kim, Jong-Min (Frontiers in Neurology, 2022)
Background: The glymphatic system has been described as one that facilitates the exchange between the cerebrospinal fluid (CSF) and interstitial fluid, and many recent studies have demonstrated its presence based on magnetic resonance imaging (MRI). We aim to systematically review the studies demonstrating a normal glymphatic system in a human population using MRI and to propose a detailed imaging protocol for the glymphatic system. Methods: We searched the MEDLINE and EMBASE databases to identify studies with human participants involving MRI-based demonstrations of the normal glymphatic system. We extracted data on the imaging sequence, imaging protocol, and the targeted anatomical structures on each study. Results: According to contrast-enhanced MRI studies, peak enhancement was sequentially detected first in the CSF space, followed by the brain parenchyma, the meningeal lymphatic vessel (MLV), and, finally, the cervical lymph nodes, corresponding with glymphatic flow and explaining the drainage into the MLV. Non-contrast flow-sensitive MRI studies revealed similar glymphatic inflow from the CSF space to the brain parenchyma and efflux of exchanged fluid from the brain parenchyma to the MLV. Conclusion: We recommended T1-weighted contrast-enhanced MRI for glymphatic system visualization. Our result can increase understanding of the glymphatic system and may lay the groundwork for developing standardized imaging protocols.